Creative aging in virtual spaces: using museum content and music therapy to explore cultural diversity - Belgrave, Melita; Palmer, Katherine; Luger Motyka, Tana M. (Frontiers in Medicine, 2023)
During the pandemic, many creative aging programs stopped being delivered in person, and practitioners turned to various virtual platforms to deliver content for older adults to maintain their cognitive, physical, and psychosocial well-being. Collaborators from a university-based music therapy program and a global music museum developed asynchronous virtual programs, one for wellness populations and another for memory care settings. The asynchronous program included museum gallery content and music therapy interventions of singing, movement, and/or instrument playing based on highlighted geographic regions. The purpose of the study was to explore older adults' experiences when participating in the program. Older adult participants were categorized as cognitively healthy (n = 27) or those diagnosed with dementia (n = 29) and attended five music sessions over eight weeks, ranging from 30-60 minutes in length. Psychosocial well-being for cognitively healthy older adults were measured with the Multicultural Quality of Life Index, Engagement in Meaningful Activity Survey, and the PROMIS Social Isolation Short Form-4a. Psychosocial well-being for older adults with memory loss was measured with the Quality of Life in Late-Stage Dementia tool. Cognitively healthy older adults showed an increase in psychological/emotional wellness after participating in the program, while older adults with memory loss appeared less irritable and physically uncomfortable and seemed to enjoy interacting with others more. Surprisingly, the cognitively healthy older adults also showed an increase in social isolation between the start and end of the program, which may not be related to the intervention, but to the fact that all three sites had COVID outbreaks during the study and had to pause their group activities programming and residents were required to stay in their rooms. Additionally, the music interventions fostered engagement behaviors of interest (facial expression, posture), and response (body movement, eye contact, and musical interaction with the leaders in the videos) for both groups of older adults.Instrument interventions were most engaging for cognitively healthy older adults. Findings suggest that creative aging virtual programs can be delivered in asynchronous settings to enhance older adults' wellbeing and foster engagement.